Impact of photobiomodulation on neural embryoid body formation from immortalized adipose-derived stem cells - Precious Earldom Mulaudzi; Heidi Abrahamse; Anine Crous (Stem Cell Research & Therapy)
Abstract Background Embryoid bodies (EBs) are three-dimensional (3D) multicellular cell aggregates that are derived from stem cell and play a pivotal role in regenerative medicine. They recapitulate many crucial aspects of the early stages of embryonic development and is the first step in the generation of various types of stem cells, including neuronal stem cells. Current methodologies for differentiating stem cells into neural embryoid bodies (NEBs) in vitro have advanced significantly, but they still have limitations which necessitate improvement. Photobiomodulation (PBM) a low powered light therapy is a non-invasive technique shown to promote stem cell proliferation and differentiation. Methods This in vitro study elucidated the effects of photobiomodulation (PBM) on the differentiation of immortalized adipose-derived stem cells (iADSCs) into NEBs within a 3D cell culture environment. The study utilized PBM at wavelengths of 825 nm, 525 nm, and a combination of both, with fluences of 5 and 10 J/cm2. Morphology, viability, metabolic activity, and differentiation following PBM treatment was analysed. Results The results revealed that the effects of photobiomodulation (PBM) are dose dependent. PBM, at 825 nm with a fluence of 10 J/cm2, significantly enhanced the size of neural embryoid bodies (NEBs), improved cell viability and proliferation, and reduced lactate dehydrogenase (LDH) levels, indicating minimal cell damage. Interestingly, the stem cell marker CD 44 was upregulated at 5 J/cm2 in all treatment groups at 24 and 96 hpi, CD105 increased with 825 nm at 10 J/cm2 at 24 hpi, which may be attributed to a heterogeneous cell population within the NEBs. Pax6 expression showed transient activation. Nestin was upregulated at 825 nm with 10 J/cm2 at 96 hpi, suggesting a promotion of neural precursor populations. GFAP an intermediate filament protein was upregulated at 825 nm at 10 J/cm2 at both 24 and 96 hpi. SOX2, a pluripotency marker, was expressed at 5 J/cm2 across all wavelengths. Neu N a neuronal nuclei marker was expressed at 5 J/cm2 in all treatments at 24 hpi and over time the expression was observed in all treatment groups at 10 J/cm2. Conclusion In conclusion, the application of PBM at 825 nm with a fluence of 10 J/cm2 during the differentiation of iADSCs into NEBs resulted in optimal differentiation. Notably, the neuronal marker Nestin was significantly upregulated, highlighting the potential of the PBM approach for enhancing neuronal differentiation its promising applications in regenerative medicine. Graphical Abstract